Phytoalexin Accumulation in Colombian Bean Varieties and Aminosugars as Elicitors (2002)
ABSTRACT: The accumulation of isoflavonoid phytoalexins was studied in several Colombian bean cultivars resistant and susceptible to Colletotrichum lindemuthianum fungus, the causal agent of anthrachnose disease. A time-course accumulation analysis on seedlings treated with CuCl2 showed that phaseollin production was higher in resistant cultivars than in susceptible ones. Also, a defensive role of phytoalexins was demostrated when extracts containing this pterocarpan exhibited antifungal activity against C. lindemuthianum. In addition, the elicitor activity of some aminosugars was also established.